«Em razão das conquistas, religião, commercio» - Cândida Barros (Mélanges de la Casa de Velázquez)
This article explores the relationships between the concepts of lingua franca and «tapuya» (those who do not speak the lingua franca) in Jesuit writings from the State of Maranhão and Grão Pará in the 17th and 18th centuries, and in the articles of Rafael Bluteau’s Vocabulario Portuguez & Latino (1712-1728). Our hypothesis is that the social category of «Tapuya» was a creation of the colonial policy of introducing a lingua franca. Aside from «Tapuya», other categories have been devised to designate the speakers of the lingua franca for instance «Nheengaíbas» and «Baré». Finally, we look at the semantic mutation of «Tapuya», which by the 18th century had finally come to designate the speakers of the lingua franca of Amazonia.